Death due to Poisoning - a Medicolegal Study at Dhaka Medical College, Dhaka - Ahmad, Mushtaq; Rahman, Farial Naima; Islam, Md Mozaharul; Majumder, Md Rakib Uddin (Faridpur Medical College Journal, 2015)
Self destruction or suicide by pesticide poisoning is a burning problem of Bangladesh. Rapid development in science and rapid growth in agricultural activities has led to the increase in the incidences of poisoning. The objective of this study was to find out the incidences and pattern of poisoning in an urban area, different aspects of poisoning along with demographic pattern, social factors related and other related perimeter, and modality to prevent loss of precious life due to poisoning. This retrospective cross sectional study was conducted among victims of poisoning at Dhaka Medical College, Dhaka Morgue during the period of January 2008-December 2009. Specific identification of poisons was made from Chemical Examiner's report. All the data were later on analyzed. A total of 5114 medico legal post mortems were performed during this study period. Among these 300 (5.87%) cases were suspected poisoning. Out of these cases specific poisons were identified in 131 (43.66%) cases. Among the detected poisoning cases OPC was the commonest agent 103 (78.63%) followed by alcohol/rectified spirit 12 (9.16%) and barbiturate 7 (5.34%). No poison was detected (Negative results) in 116 (38.66%) cases and no reports from chemical examiner were received in 53 (17.66%) cases during the study period. Out of 300 victims 174 (58%) were male and 126 (42%) were female. Highest incidence of poisoning was observed in 21-30 years age group 117 (39%) followed by age group of 31-40 years 84 (28%). Most of the victims were agricultural workers/ farmers 108 (36%) followed by housewives 51 (17%). Among the study subjects 178 (59.33%) were illiterate and 198 (66%) were married. Considering manner of death 274 (91.33%) victims committed suicide by poisoning and rests 26 (8.67%) were due to accidental poisoning. To reduce poisoning cases proper emphasis should be given for safe use of pesticides and consciousness should be created among the population about poisonous compounds. Detail study regarding death due to poisoning is required to be carried out in this country. Faridpur Med. Coll. J. 2014;9(2): 76-79